2020
DOI: 10.3390/app10249111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mat Pilates on Body Fluid Composition, Pelvic Stabilization, and Muscle Damage during Pregnancy

Abstract: In this study, according to the exercise intensity (50–60% of HRmax (Maximum Heart Rate), RPE (Rating of Perceived Exertion: 11–13) proposed by The American Congress of Obstetricians and Gynecologists (ACOG) for pregnant women, mat Pilates exercise is related to body composition, lipid parameters, and pelvic stabilization. The effects on muscle and muscle damage were investigated. The subjects of this study were 16 pregnant women registered at the Cultural Center of Gyeonggi-do C Women’s Hospital, and the gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…However, excessive weight gain causes complications such as hypertension, diabetes, and hyperlipidemia, thus necessitating proper diet control and exercise [ 33 , 34 ]. Pilates is reportedly effective at controlling body weight and body fat in pregnant women and facilitates childbirth by increasing the skeletal muscle mass [ 35 ]. Thus, we aimed to confirm whether HTPE triggered changes in body fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive weight gain causes complications such as hypertension, diabetes, and hyperlipidemia, thus necessitating proper diet control and exercise [ 33 , 34 ]. Pilates is reportedly effective at controlling body weight and body fat in pregnant women and facilitates childbirth by increasing the skeletal muscle mass [ 35 ]. Thus, we aimed to confirm whether HTPE triggered changes in body fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to those of previous studies that have reported loss in body fat after Pilates exercise. In addition, resistance movements, such as the contraction and relaxation of skeletal muscles, along with a Pilates-induced reduction in body fat increase the SMM and muscle strength [ 35 ]. Accordingly, an HTPE-mediated increase in the SMM would likely occur.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancy, musculoskeletal changes can be encountered frequently and these changes are affected by physical activities (3,4). In Hyun and Jeon's Study, ıt was found that Pilates increase skeletal muscle and does not cause muscle damage in pregnant women (20). In this study, examining the women's complaints related to the musculoskeletal system in pregnancy; only one woman stated that she had cramps during her pregnancy.…”
Section: Discussionmentioning
confidence: 65%
“…In the literature, studies on Pilates in pregnant women are insufficient and additional verification in needed (6). In this study was found that prenatal pilates had greater emotional and mental advantages, whereas the least advantageous process was the moment of childbirth.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation